2020
DOI: 10.1177/1533033820948062
|View full text |Cite
|
Sign up to set email alerts
|

ESTAT3 Inhibitor AG-490 Inhibits the Growth of Prostate Cancer by miR-503-5p Both In Vivo and In Vitro

Abstract: Objective: To explore the effect and the related mechanism of STAT3 inhibitor AG-490 on inhibiting the proliferation of prostate cancer cells. Methods: PC3 cells and DU145 cells were cultured stably and treated with AG-490 to detect the changes in the activity of PC3 cells and DU145 cells. Thirty 6-8 weeks male BALB/c nude mouse were randomly divided into a control group, a DMSO group, and an AG-490 group to detect differences in various indexes . Results: The overexpression of miR-503-5p depends on the activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…It was notable that the two identified miRNAs have previously been described in PCa and in other cancers. A recent study demonstrated that a change in the level of expression of the miRNA hsa-miR-503-5p is associated with the degree of differentiation of tumor cells in PCa [ 22 ]. Upregulation of hsa-miR-503-5p in BCR cases may be associated with a decrease in the expression of PTEN , TIMP3, and PDCD4 and activation of the AKT signaling pathway [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was notable that the two identified miRNAs have previously been described in PCa and in other cancers. A recent study demonstrated that a change in the level of expression of the miRNA hsa-miR-503-5p is associated with the degree of differentiation of tumor cells in PCa [ 22 ]. Upregulation of hsa-miR-503-5p in BCR cases may be associated with a decrease in the expression of PTEN , TIMP3, and PDCD4 and activation of the AKT signaling pathway [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that a change in the level of expression of the miRNA hsa-miR-503-5p is associated with the degree of differentiation of tumor cells in PCa [ 22 ]. Upregulation of hsa-miR-503-5p in BCR cases may be associated with a decrease in the expression of PTEN , TIMP3, and PDCD4 and activation of the AKT signaling pathway [ 22 ]. TIMP3 is an inhibitor of MMP , and, when it is suppressed, MMP2 is activated, this being involved in the destruction of the extracellular matrix, which, therefore, probably promotes cell motility, inducing migration and invasion [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A transwell chamber with an 8-µm pore size polycarbonate membrane (Corning, NY) was used to evaluate cell migration. After 48h of transfection, the PCa cells were resuspended with basic medium and seeded into the upper chamber (2×10 4 for PC-3 cells and 5×10 4 for LNCaP cells), while culture medium containing 15% FBS was added to the lower chamber. After incubation for 48 h at 37°C, the medium was removed from the upper chamber, and non-migrated cells were scraped off with a cotton swab.…”
Section: Cell Migration and Invasion Assaymentioning
confidence: 99%
“…Thus, in-depth understanding of the mechanism of metastatic PCa will help us intervene and treat of PCa patients better. Previous studies have con rmed that the malignant progress of PCa is a multi-step and multi-stage progress, which is involved with the dysregulation of multiple molecules, including miRNAs [4][5][6].…”
Section: Introductionmentioning
confidence: 99%